(untitled) (Tzintzun, Revista de Estudios Históricos, 2024)
The present work studies and analyzes six books of the sick and two books of the sick of the Hospital Juanino de Nuestra Señora de los Desamparados of the city of Tezcoco elaborated in theXVIII century; but it focuses its attention on three important epidemics that struck the local population in 1737 (Matlazahuatl), 1784 (Influenza) and 1813 (Typhus). These manuscripts have remained in historiographic oblivion and their analysis allows us to know the ages, origin and “sickness” that were treated in a hospital during the eighteenth century.